2021
DOI: 10.1002/rra.3894
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of the Doce River Basin after the Fundão dam collapse: What has been done, what can be done and what should be done?

Abstract: Five years after the failure of the Fundão Dam in Brazil, no scientific report has been published regarding the rehabilitation interventions performed by the Renova Foundation, which is solely responsible for the rehabilitation of the Doce River Basin. This study aimed to assess the fluvial and riparian rehabilitation efforts performed by Renova, as well as to test and propose alternatives, when appropriate. Before the dam rupture, the fluvial system showed a single‐thread morphology that was sinuous and meand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These results showed that zone 1 and 3 presented a higher preservation degree than zone 2 where it was found the dominance of invasive species. Cordeiro et al 2021 observed also the worsening of NDVI index after Fundão dam disaster what was followed by increase of invasive and pioneer species such as Brachiaria sp and Ricinus communis [9].…”
Section: Resultsmentioning
confidence: 92%
“…These results showed that zone 1 and 3 presented a higher preservation degree than zone 2 where it was found the dominance of invasive species. Cordeiro et al 2021 observed also the worsening of NDVI index after Fundão dam disaster what was followed by increase of invasive and pioneer species such as Brachiaria sp and Ricinus communis [9].…”
Section: Resultsmentioning
confidence: 92%
“…These results showed that zone 1 and 3 presented a higher preservation degree than zone 2 where it was found the dominance of invasive species. Cordeiro et al 2021 observed also the worsening of NDVI index after Fundão dam disaster what was followed by increase of invasive and pioneer species such as Brachiaria sp and Ricinus communis [9].…”
Section: Resultsmentioning
confidence: 98%